A review of the recent advances in heat transfer through ducting in the rotational moulding process and the future trends - Sutirtha Chowdhury; Jayantha Epaarachchi; Ahmad Sharifian-Barforoush; Md Mainul Islam (International Journal of Thermofluids)
A common technique for producing large-scale hollow plastic items is rotomoulding. Rotation speed, mould design, and temperature management significantly affect the quality of finished products. A production peak in the rotomoulding business is imminent due to the increasing demand. Though theoretical and experimental data from the previous studies regarding rotational moulding validate their hypothesis but lack of information about practical usage while production time evolves questions about the accuracy and efficiency of innovations. Meanwhile, the lack of sufficient research on the phase transition from the heat source for the rotomoulding procedure led to a great research gap in this field. Nevertheless, conclusions are of substantial value to the subject matter; however, previous studies cannot be regarded as precise in the analysis. Consequently, the review paper sought to emphasise the increasing challenges, such as temperature variation, air leakage, pressure drop, and improved heat distribution techniques. The first phase of the paper involves a discussion and analysis of research findings from the previous decade. The enhancement of the mould area is being proposed based on previous findings to improve heat efficiency. In the second phase, the authors aimed to provide insights into enhancing heat transfer within the ducting system of a rotomoulding oven by exploring duct designs, implementing FADS, and optimising insulation techniques, all while minimising carbon emissions in the process. In addition, the cost-effectiveness of ducted ovens, enhanced insulation processes, and the selection of insulation materials based on oven configuration will yield benefits for rotomoulders in the near future. The authors presented the economic advantages of installing an appropriate ducting system in a rotational moulding machine oven, demonstrating a net annual savings of 12.7 % and a short payback period for an additional investment.